2020
DOI: 10.1371/journal.pone.0229959
|View full text |Cite
|
Sign up to set email alerts
|

Low hemoglobin increases risk for cerebrovascular disease, kidney disease, pulmonary vasculopathy, and mortality in sickle cell disease: A systematic literature review and meta-analysis

Abstract: Sickle cell disease (SCD) is characterized by deoxygenation-induced polymerization of hemoglobin in red blood cells, leading to hemolytic anemia, vaso-occlusion, and the development of multiple clinical complications. To characterize the clinical burden associated with differences in hemoglobin concentration and hemolysis measures, a systematic literature review of MEDLINE, EMBASE, and related meta-analyses was undertaken. For quantitative analyses related to hemoglobin concentration, pooled results were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 66 publications
2
32
0
1
Order By: Relevance
“…In particular, hemolysis is established as a primary driver of disease severity partly as a result of studies associating anemia (as a surrogate marker of hemolysis) with the aforementioned sequelae, as well as with increased mortality. 14 19 Similar associations have been found for other markers of hemolysis, in particular lactate dehydrogenase, indirect bilirubin, cell-free plasma hemoglobin, and red blood cell-derived microparticles. 15 Although the degree of chronic hemolysis varies widely from patient to patient, its essential importance to the pathobiology of SCD does not, as the endothelial activation and vascular damage caused by the release of intra-corpuscular elements drive the increased cellular adhesion, inflammation, and disturbed rheology behind the ischemia–reperfusion damage that characterizes the disease.…”
Section: Anemia In Sickle Cell Diseasesupporting
confidence: 65%
“…In particular, hemolysis is established as a primary driver of disease severity partly as a result of studies associating anemia (as a surrogate marker of hemolysis) with the aforementioned sequelae, as well as with increased mortality. 14 19 Similar associations have been found for other markers of hemolysis, in particular lactate dehydrogenase, indirect bilirubin, cell-free plasma hemoglobin, and red blood cell-derived microparticles. 15 Although the degree of chronic hemolysis varies widely from patient to patient, its essential importance to the pathobiology of SCD does not, as the endothelial activation and vascular damage caused by the release of intra-corpuscular elements drive the increased cellular adhesion, inflammation, and disturbed rheology behind the ischemia–reperfusion damage that characterizes the disease.…”
Section: Anemia In Sickle Cell Diseasesupporting
confidence: 65%
“…57 For example, a systematic literature review analyzed published data from multiple sources (e.g., clinical trials and RWE from registries) to understand how hemoglobin concentration (a biomarker) is related to various clinical endpoints, such as stroke, cerebrovascular disease, kidney disease, pulmonary vasculopathy, and mortality in patients with sickle cell disease. 58 Based on a meta-analysis of these data, researchers concluded that changes in hemoglobin concentration are a validated intermediary measure of disease progression in patients with sickle cell disease.…”
Section: Selection Of Endpoints and Identification Of Surrogate Endpointsmentioning
confidence: 99%
“…The flow rates evaluated by TCD were correlated with severity of anemia [ 10 ]. Similarly, low hematocrit and hemoglobin levels were associated with complications of the disease [ 11 ]. It is therefore interesting to assume that changes in the velocities identified by TCD examination may reflect the severity of SCA.…”
Section: Introductionmentioning
confidence: 99%